Estudo da oxidação preferencial do CO por catalisadores a base de irídio - Silva Júnior, Waldir da (2014)
Ir/Al2O3 samples were prepared to evaluate the influence of the particle size of the metal in the preferential oxidation of CO reaction. Initially, samples with different amounts of iridium were prepared in an attempt to get different particle sizes. Samples containing 1, 2, 6 and 10 % Ir/Al2O3 were prepared. The samples were prepared via dry impregnation, from alcoholic solutions of the salt precursor and calcined at a temperature of 400 °C. The -Al2O3 support was calcined at 550 °C. The catalytic tests were carried out using a flow rate of 100 ml/min of a mixture containing 1% O2, 1% CO, 45% H2 and balance in He. The results of XRD of these samples showed no characteristic peaks of iridium and the metal dispersions were very similar, raising the possibility that even with the increased loading of iridium samples showed no significant differences in their structure. After realize catalytic tests using the same density of active sites, it was found that the structure of the samples was very similar and the different results of activity and selectivity were due to the different densities of active sites. In order to obtain samples with different structural properties, was fixed in 4% the iridium concentration on the catalysts and was varied the calcination temperature of the catalysts (400, 550 and 750 °C) and the support (550 and 750 °C) and was studied the influence of calcination temperature of the catalyst as well the support. Results of XRD and hydrogen chemisorption showed large differences in particle size and metal dispersion. The total flow of the catalytic tests was reduced to 50 mL/min, maintaining the concentrations of the gases. DRIFTS spectra confirmed the structural differences due to the increase of calcination temperature of catalysts, showing a large decrease in the interaction between CO/metal. The results of the catalytic tests showed that by increasing the calcination temperature of the catalysts there is a loss of activity but these catalysts were more selective. A strong influence of the calcination temperature of the supports in the activity and selectivity of the catalysts was also observed. The results show that the PROX reaction is very sensitive to catalyst structure.